Estudio de factibilidad para la creación de un centro de rehabilitación para personas con capacidades especiales para el cantón Las Lajas, provincia de El Oro - Moncada Jaramillo, Mayenci Macrina (2015)
The present study was conducted in the city of Las Lajas province of El Oro, with the overall objective to determine the feasibility of installing a Rehabilitation Centre for disabilities (Physical and Mental Disabilities) in the city of Las Lajas province of El Oro. This involved the use of various methods such as scientific, analytical, inductive, hypothetical - deductive and techniques such as direct observation, interview and survey that allowed them to gather relevant information for this project. Thus being able to perform market research where basically the survey was applied to 283 participants of the program for the control of Disabilities (PWD) .Health Ministry of Health Center, features the Cato Las Lajas, the same as applied to the families of people with intellectual disabilities, potential service users own rehabilitation and disabled with physical disabilities. Within the technical study could determine the capacity that will be effective 247 patients and a capacity utilization of 80% for year 3072 with demand services for the first year. We also determined the macro and micro - location of the company, as it was noted that the market defined there are people who require this service. In addition there are infrastructural conditions and skilled labor for effect. In the organizational study we determined the constitution of the company, same as company name will Centro de Rehabilitation” Las Lajas CIA LTDA”, and will be limited company in which the partners are liable for the amount of their contributions; staff working in the administrative part will be the ideal in such a manner that contributes to the achievement of organizational objectives The financial study allowed us to determine that the implementation of the company is advisable. As the total investment for this project will be $38.191,85 the unit cost of service provided constitutes $10,37; list price is $12,85 with a profit margin of 25% for the first year net income generated $ 12,263, 91. The economic evaluation gave a positive NPV of $ 16. 349.56, IRR exceeds the cost of capital of 27.6%, an Benefit-Cost 25 cents for every dollar invested, the investment is recovered in two years, 7 months and 25 days and finally got the project can withstand elevated costs of 13.20% and a reduction of revenues 10,56%. The analysis in the development of each of the phases of the project feasibility allowed to reach the general conclusion that if the creation and installation of the company is feasible. Based on the results, it is recommended to implement the project as it will give a significant return for its investors and a solution to the problem of disability in the Cato slabs province of El Oro, also contribute the generation of jobs